Contributing factors to decline in physical activity among adolescents: a scoping review - Normawati Ahmad; Hasnor Hadi Asim; Nurashma Juatan; Nor Ezra Hipni; Nurbaidurrah Ithnain; Nor Haryati Ahmad Sanusi; Siti Nur Farhana Harun; Muhammad Ridzwan Zakaria; Norrafizah Jaafar; Mohd Haazik Mohamed; Siti Hajar Suraji; Manimaran Krishnan (Secholian Publication, 2021)
It is presumed that the level of physical activity (PA) declines during a person’s lifespan, particularly during adolescence. The main objective of this scoping review is to summarize and identify the current literature that addresses contributing factors related to adolescent physical inactivity. This scoping review was carried out using the framework suggested by Arskey and O'Malley. The literature review was undertaken using the reference period between 2008 and 2014, based primarily on the PubMed, Cochrane and Embase databases. Additional studies have been identified by a manual bibliography search. Search term included adolescent / youth / teenage, factors / determinants /correlations, and physical inactivity/decline exercise. A total of 23 studies met the inclusion criteria. This scoping review found some evidence of the association between physical inactivity and the following variables: Age, sex, socio-economic status, lack of social support from parents, family and friends have had an impact on their motivation to perform PA on a continuous basis. Also, the lack of awareness, attitudes, and practices of individuals themselves for not doing PA has affected their interest in maintaining PA. It is noted that the environment also plays an important role, such as inadequate facilities and facilities, as well as an unsuitable place or setting that is unconducive and a neighbourhood that does not take care of or is aware of a healthy lifestyle, is also a contributing factor to physical inactivity. The decline in PA during adolescence is a consistent finding in the literature. However, PA interventions should be developed through education, family programs, behavioural or environmental and policy changes.